Prinsip Pendidikan Agama Kristen Dalam Keluarga Bagi Keluarga Banua Niha Keriso Protestan (BNKP) Hosiana - Sadiria Gulo (JURNAL GLOBAL EDUKASI, 2017)
Abstract: The problems in this research are the lack of parental responsibility in educating and growing the faith of the child. The purpose of this study is to explain how Christianity's principle of Christian Religion is based on Deuteronomy 6: 4-13 to every member of the Christian family and to explain how to build a Christian religious education in the family to every member of the Christian family. Research subjects undertaken by researchers is about the Christian family of BNKP Hosiana Church congregation. From the interviews that the authors found there are some things that hinder the Christian family does not apply the principle of Christian Religious Education in the family based on Deuteronomy 6: 4-13, namely: less time, limited time, laziness, procrastination, occupation, occupation, temptation / problems, can not control the emotions, the background of parental faith and the low awareness of parents of the importance of the introduction of God for children from an early age. Keywords: repetition, BNKP, Christian religious education Abstrak: Permasalahan dalam penelitian ini adalah Kurangnya tanggugjawab orang tua dalam mendidik dan menumbuhkan iman anak. Tujuan dari penelitian ini untuk menjelaskan bagaimana prinsip Pendidikan Agama Kristen berdasarkan Ulangan 6:4-13 kepada setiap anggota keluarga Kristen dan untuk menjelaskan bagaimana cara membangun pendidikan Agama Kristen dalam keluarga kepada setiap anggota keluarga Kristen. Subyek penelitian yang dilakukan oleh peneliti adalah seputar keluarga Kristen jemaat Gereja BNKP Hosiana. Dari hasil wawancara yang penulis dapatkan ada beberapa hal yang menjadi penghambat keluarga Kristen tidak menerapkan prinsip Pendidikan Agama Kristen dalam keluarga berdasarkan Ulangan 6:4-13, yakni: waktu yang kurang, waktu terbatas, kemalasan, menunda-nunda, pekerjaan, kesibukkan, cobaan/ masalah, belum bisa mengendalikan emosi, latar belakang iman orang tua dan rendahnya kesadaran orangtua akan pentingnya pengenalan Tuhan bagi anak sejak dini. Kata kunci: ulangan, BNKP, pendidikan agama kristen